Transformasi Peradaban Dinasti Abbasiyah Perspektif Sejarah Kebudayaan Islam - Husen Akbar Sarifudin; Irsyadi, Haidar; Mulyadi; Abbas, Ngatmin (Samodra Ilmu: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2024)
This study aims to examine the establishment process and factors driving the rise of the Abbasid Dynasty, as well as its impact on Islamic civilization. The Abbasid Dynasty, which was founded in 750 M after overthrowing the Umayyad Dynasty, became one of the largest caliphates in Islamic history. This research employs a qualitative method with a historical approach. The analysis is conducted using both primary and secondary sources to provide an in-depth understanding of the subject matter. Primary sources include original documents, records, and firsthand accounts related to the topic, while secondary sources consist of scholarly articles, books, and previous research that provide contextual and analytical insights. The combination of these sources ensures a comprehensive exploration of the historical and cultural dimensions relevant to the research. The focus of this study is on the political, social, and economic factors that contributed to the formation of the Abbasid Dynasty, including the role of non-Arab groups and rebellions supported by the mawali. The findings indicate that the Abbasid Dynasty succeeded in creating major changes in the Islamic governance structure and expanded Islamic influence in various fields, including science, culture, and trade. The significant impact on Islamic civilization is evident from the scientific and cultural advancements during the Abbasid reign, known as the